“Out of office”: Availability norms and feeling burned out during the COVID-19 pandemic: The mediating role of autonomy and telepressure - Hendrikx, Karolien; Van Ruysseveldt, Joris; Proost, Karin; van der Lee, Sandra (Frontiers in Psychology, 2023)
Introduction Digital innovations make it possible to work anywhere and anytime using any kind of device. Given these evolutions, availability norms are emerging at work. These norms specifically refer to the experienced beliefs or expectations from colleagues or superiors to be available for work-related communication after regular work hours. We rely on the Job-Demands Resources Model as we aim to investigate the relationship between these availability norms and burnout symptoms during the COVID-19 pandemic. We first of all study to what extent availability norms are associated with heightened burnout symptoms. Secondly, we study how both a personal demand, namely telepressure, and a job resource, namely autonomy, could offer distinct and relevant explanations for the role these availability norms play in experiencing burnout symptoms. Method We collected data through a survey study with 229 employees from various organizations in the second half of 2020. Results The findings indicated that indeed availability norms are significantly associated with more burnout symptoms and that both heightened telepressure and reduced autonomy mediated this relationship. Discussion This study contributes to theory and practice as we offer insight into how availability norms at work could be detrimental for the occupational health of employees, which can be taken into account when setting up rules and regulations at work.